Epidemiological features of dengue fever and envelope gene of dengue virus among imported and indigenous cases in Guangzhou city: a comparison analysis on registry data of 2019 - Li-yun JIANG; Yuan LIU; Wen-zhe SU (Editorial Office of Chinese Journal of Public Health, 2022)
ObjectiveTo assess epidemiological features of imported and indigenous dengue fever cases and phylogenetic features of dengue virus prevalent in the cases in Guangzhou, Guangdong province in 2019 and to explore the impact of imported cases on dengue fever epidemics in the city. MethodsThe data on all dengue fever cases registered in Guangzhou city in 2019 were extracted from the National Notifiable Infectious Disease Reporting System. The demographic and epidemiological features of the reported cases were statistically analyzed. The envelope (E) gene of the dengue viruses isolated from the cases was sequenced and analyzed to construct maximum likelihood phylogenetic trees. ResultsAmong 1655 dengue fever incidents yearly registered in the city, 273 and 1 382 were imported and local cases. Of the imported cases with a male to female ratio of 2.85 : 1, 86.45% were aged 20 to 49 years, mainly being engaged in commercial service, housework and general industries. The imported cases occurred in every month of the year but more cases were reported during June and August. The most (90.38%) of the imported cases were from Southeast Asia. For the reported local dengue fever cases, the male to female ratio was 1.07 : 1 and 89.87% were at ages of 20 - 69 years; main occupations of the local cases included houseworker, unemployee, commercial service worker and retiree; the local cases were reported during June - December and more cases were reported during August - October of the year. E gene sequences of the virus isolated from the local cases displayed close associations with sequences from imported cases and with those of prevalent virus in Southeast Asia. ConclusionThe epidemic of dengue fever in Guangzhou city was affected by the imported dengue fever cases and the local prevalence of dengue fever in 2019 was likely being induced by the imported cases.